(untitled) (Jurnal Ilmiah Psikologi MIND SET, 2024)
The increasing responsibilities and demands faced by university students often make them vulnerable to depressive symptoms. A study was conducted to explore how self-compassion affects depressive symptoms among students, with resilience playing a mediating role. The study involved 200 university students (164 females) from a university in Jakarta. Mediation analysis was performed using the MedMod module with bootstrap estimation method, using 1000 resamples to estimate mediation effects and establish 95% confidence intervals. The results indicated that resilience partially mediated the relationship between self-compassion and depression. Students with higher self-compassion tend to be less self-critical when facing failure, perceive difficult situations as something that can happen to anyone, and maintain a balanced perspective without overgeneralizing. These characteristics of self-compassion enhance resilience, which in turn contributes to reducing depressive symptoms during challenging times.